Analysis of Statistical Thinking Ability of Mathematics Students Based on Artist Test - Hadi Kusmanto (EduMa: Mathematics education learning and teaching, 2023)
This study aims to determine the statistical thinking skills of mathematics students and their differences based on gender, school origin, and semester level. To map the statistical thinking skills using the modified Artist test standards. The development of students' statistical thinking skills is one of the focuses of learning mathematics in Higher Education. Students' statistical thinking ability is absolutely necessary to be able to think scientifically. Statistical thinking is the ability to think inductively. The population in this study were all mathematics students, while the sampling was based on proportional random sampling. The data analysis technique uses the t-test, Anova, and Least Significance Difference (LSD) as a follow-up test. Based on the results of the analysis carried out, it was found that students 'statistical thinking skills were classified as low which was below the value of 60 on a scale of 100. These results indicated that students' statistical thinking skills were still low, especially the ability to communicate data and draw conclusions. Another result shows that there is a difference in the ability to think statistically at the semester level, while there is no difference between sex and school origin. For semesters, third-semester students do better than other semesters